Dirty beasts - Dahl, Roald; Blake, Quentin (Puffin London, 2001)
A collection of humorous poems about amazing or nasty creatures, including a flying cow, a pig who turns the tables on a farmer, and crocodiles, lions, and anteaters who delight in devouring people